A sorting nexin-1 homologue, Vps5p, forms a complex with Vps17p and is required for recycling the vacuolar protein-sorting receptor. - Horazdovsky, B F (1997)
A number of the Saccharomyces cerevisiae vacuolar protein-sorting (vps) mutants exhibit an altered vacuolar morphology. Unlike wild-type cells that contain 1-3 large vacuolar structures, the class B vps5 and vps17 mutant cells contain 10-20 smaller vacuole-like compartments. To explore the role of these VPS gene products in vacuole biogenesis, we cloned and sequenced VPS5 and characterized its protein products. The VPS5 gene is predicted to encode a very hydrophilic protein of 675 amino acids that shows significant sequence homology with mammalian sorting nexin-1. Polyclonal antiserum directed against the VPS5 gene product detects a single, cytoplasmic protein that is phosphorylated specifically on a serine residue(s). Subcellular fractionation studies indicate that Vps5p is associated peripherally with a dense membrane fraction distinct from Golgi, endosomal, and vacuolar membranes. This association was found to be dependent on the presence of another class B VPS gene product, Vps17p. Biochemical cross-linking studies demonstrated that Vps5p and Vps17p physically interact. Gene disruption experiments show that the VPS5 genes product is not essential for cell viability; however, cells carrying the null allele contain fragmented vacuoles and exhibit defects in vacuolar protein-sorting similar to vps17 null mutants. More than 95% of carboxypeptidase Y is secreted from these cells in its Golgi-modified p2 precursor form. Additionally, the Vps10p vacuolar protein-sorting receptor is mislocalized to the vacuole in vps5 mutant cells. On the basis of these and other observations, we propose that the Vps17p protein complex may participate in the intracellular trafficking of the Vps10p-sorting receptor, as well as other later-Golgi proteins.